Socialization of MSME Taxation through Booklet Media: Increasing Tax Compliance among MSMEs with Aspikmas - Asausan, Iftifani Sayyida; Huwaida, Isna; Ramadhan, Rafli Hafiz; Wibowo, Anang; Zamzam D.R, Muhammad; Restianto, Yanuar E. (Asian Journal of Community Services, 2024)
Most people, as business owners, run businesses in the Micro, Small, and Medium Enterprises (MSMEs) sector and strive to continue to increase their income and business profits without understanding the tax burden that will arise. Therefore, understanding taxes is very important for students and entrepreneurs, individuals, and all levels of society. This study aims to explore the understanding and tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Banyumas Regency, who are members of the Aspikmas Association. Using a descriptive qualitative approach, data was collected through in-depth interviews, field observations, and documentation. The results indicate that while MSME tax compliance is generally good, more socialization is needed to enhance their understanding of tax regulations, particularly in terms of annual tax return reporting.